AB0093 Association of cd247 polymorphisms with rheumatoid arthritis: a replication study and a meta-analysis. (23rd January 2014) - Teruel, M.; McKinney, C.; Balsa, A.; Pascual-Salcedo, D.; Rodriguez-Rodriguez, L.; Ortiz, A. M.; Gómez-Vaquero, C.; González-Gay, M. A.; Smith, M.; Witte, T.; Merriman, T. R.; Lie, B. A.; et al.
Abstract : Background: The T-cell receptor T3 zeta chain ( CD3 ζ), also called CD247, is essential for assembly, surface expression and signaling cascade of the T-cell receptor-CD3 complex (TCR/CD3 complex). Abnormalities in this pathway can result in T-cell dysfunction and development of autoimmune disorders [1 ]. Regarding this, previous reports have demonstrated an association of CD247 variants with systemic lupus erythematosus [2, 3 ] and systemic sclerosis [4, 5 ]. In the case of rheumatoid arthritis (RA), one meta-GWAS found no association between CD247 gene and RA at a genome-wide level of significance [6 ], however, a more recent meta-analysis of GWAS on RA and celiac disease (CeD) identified CD247 gene as a new susceptibility locus for RA [7 ]. Objectives: In order to better clarify the role of this gene in RA susceptibility, we aimed to analyze CD247 gene variants previously associated with other autoimmune diseases (rs1052237, rs2056626 and rs864537) in a large independent European Caucasian population. Results: However, no evidence of association was found for these three CD247 SNPs with RA and with the anti-cyclic citrullinated polypeptide (anti-CCP) status. We performed a meta-analysis including GWAS data for the rs864537 from previously published data, reveling an overall genome-wide significant association between rs864537 and RA with anti-CCP (OR 0.90 [0.87 to 0.93], Poverall = 2.1 x 10 -10 ). Conclusions: Our results described for first time at GWAS-level the association of this CD247 variant and RA risk References: Takeuchi T et al . Ann Rheum Dis . 2012; 71:i78-i81. Gorman CL et al . J Immunol . 2008; 180: 1060-70. Warchol T et al . Tissue Antigens . 2009; 74:68-72. Dieude P et al . Ann Rheum Dis . 2011;70:1695-6. Radstake TR et al . Nat Genet . 2010; 42:426-9. Stahl EA et al . Nat Genet . 2010; 42:508-14. Zhernakova A et al . PLoS Genet . 2011; 7:e1002004. Acknowledgements: This work was supported by two Spanish grants from RETICS Program, RD08/0075 (RIER) from Instituto de Salud Carlos III (ISCIII), within the VI PN de I+D+i 2008-2011 (FEDER) and also by grants from the European IMI BTCure Program. MT was supported by Spanish Ministry of Science through the program Juan de la Cierva (JCI-2010-08227). Disclosure of Interest: None Declared